Brecht in Turkey 1955-1977 The Impact of the Bertold Brecht on Society and the Development of Revolutionary Theater in Turkey - Nekimken, Albert (Analecta Isisiana: Ottoman and Turkish Studies, 2010)
A study of the role of the German playwright Brecht on Turkish society and thinking in the twentieth century